Errors and disfluencies in spoken corpora - Gilquin, Gaëtanelle (Benjamins current topics, 2013)
Individual speakers vary considerably in their rate of speech, their syntactic choices, and the organisation of information in their discourse. This study, based on a corpus of monologue productions from native and non-native speakers of English and French, examines the relations between temporal fluency, syntactic complexity and informational content. The purpose is to identify which features, or combinations of features, are common to more fluent speakers, and which are more idiosyncratic in nature. While the syntax of fluent speakers is not necessarily more complex than that of less fluent.